Circulating Exosomes Activate Dendritic Cells and Induce Unbalanced CD4+ T Cell Differentiation in Hashimoto Thyroiditis - Cui, Xuejiao; Liu, Yongping; Wang, Shuo; Zhao, Na; Qin, Jing; Li, Yushu; Fan, Chenling; Shan, Zhongyan; Teng, Weiping (The journal of clinical endocrinology and metabolism, 2019)
Abstract Objective This study explored whether circulating exosomes effectively participate in the inflammatory response in Hashimoto thyroiditis (HT). Design Exosomes were extracted from the serum of 30 patients with HT and 30 healthy control (HC) subjects. The expression of thyroperoxidase (TPO), thyroglobulin, high mobility group box 1 (HMGB1), heat shock protein 60 (HSP60), major histocompatibility complex class II (MHC-II), and intercellular adhesion molecule 1 (ICAM1) in exosomes was determined by Western blotting. Flow cytometry and immunofluorescence were performed to confirm that exosomes were taken up by healthy peripheral blood mononuclear cells (PBMCs) and dendritic cells (DCs). Then, either DCs or PBMCs were stimulated with HT exosomes (serum exosomes from patients with HT) or HC exosomes (serum exosomes from HC subjects) in the presence or absence of Toll-like receptor (TLR)2/3 inhibitors. Results TPO, HSP60, and MHC-II expression was higher in HT exosomes than in HC exosomes. Exosomes were mainly taken up by CD14+ monocytes and CD11c+ DCs. After DCs were stimulated by HT exosomes, significant elevations were observed in MyD88, TRIF, and p-P65 expression; median fluorescence intensity of CD40 and CD83; and IL-6 production. After stimulating PBMCs with HT exosomes, CD11c+TLR2+/TLR3+ and CD4+IFN-γ+Th1/IL-17A+Th17A cell percentages were significantly elevated, and CD4+CD25+Foxp3+ Treg cell percentage was significantly decreased. HT exosomes induced increased IL-17A and IFN-γ production, whereas IL-10 production was suppressed. However, addition of TLR2 or TLR3 inhibitor reversed most of the abovementioned results. Conclusions Our study demonstrates that HT exosomes can present antigens to DCs and bind TLR2/3, causing DC activation via the nuclear factor κB signaling pathway, leading to an imbalance in CD4+ T lymphocyte differentiation, and potentially contributing to HT onset. HT exosomes, which carry HSP60, TPO, and MHC-II, are believed to activate DCs via the TLR2/MyD88/NF-κB and TLR3/TRIF/NF-κB pathways, causing an imbalance in the differentiation of CD4+ T lymphocytes.